Pemanfaatan Konsep Ekohidrologi (Penciptaan Air dan Sanitasi Bersih) Sebagai Upaya Mengatasi Stunting di Desa Bulang - Husni Mubaroq (Abdi Panca Marga, 2019)
Ecohydrology is an approach to integrated water resources management that offers a sustainable development approach in understanding the environment and water resources systems. In this case the conditions where clean water and food can be created to reduce the number of stunting in an area. The concept of ecohydrology can also prevent the spread of disease through water. The introduction of this concept is intended to reduce stunting and overcome the lack of clean water in the future. In this case the concept of Ecohydrology is offered with the existing water purification plan to produce clean water that is ready to use and utilizes materials that are easily available and have low prices. Keywords: Stunting, ecohydrology concept